Piranske notarske knjige (Zvezek 6) = The Notary Book from Piran (Vol. 6) Fragmenti (1298-1317) = Fragments (1298-1317) - Mihelič, Darja (Thesaurus memoriae, 2016)
With notary books we are not dealing with literary readings, but with abstracts of a mass of business manuscript agreements of various contents. The subject of this publication is the preserved parts of the third, ninth, and tenth notary fascicles from the Piran Branch Office of the Regional Archives of Koper. The fragments contain the models of documents created in the period 1284-1296. The authors of summaries in the preserved fragments of notary fascicles are Facina Grimaldi, Facina (Vitali?) and Francisscus de Malonbris.